The Dynamics of Illiteracy Formation in India - Pietkiewicz-Pareek, Beata (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
India is one of the fastest growing countries in the world. At the sametime, there are 272, 700, 941 illiterate people in India, most of who mare marginalized by factors such as poverty, gender, disability, and caste. Children are often forgotten, remaining invisible in the strictly hierarchical Indian society. Access to education reserved for the highest castes has led to marginalization of the lowest castes, especially untouchable Dalits. This paper deals with illiteracy in India, its causes and the barriers to overcoming it that lie within the society. The aim is to inform the reader about the problem of discriminationin education which leads to illiteracy.
Keywords: illiteracy; India; education; Dalits; educational policy